Low‐level expression of EPG5 leads to an attenuated Vici syndrome phenotype. Issue 5 (21st April 2018) - Waldrop, Megan A.; Gumienny, Felecia; Boue, Daniel; de los Reyes, Emily; Shell, Richard; Weiss, Robert B.; Flanigan, Kevin M.
Abstract : Vici syndrome is a multisystem disorder characterized by agenesis of the corpus callosum, oculocutaneous hypopigmentation, cataracts, cardiomyopathy, combined immunodeficiency, failure to thrive, profound developmental delay, and acquired microcephaly. Most individuals are severely affected and have a markedly reduced life span. Here we describe an 8‐year‐old boy with a history of developmental delay, agenesis of the corpus callosum, failure to thrive, myopathy, and well‐controlled epilepsy. He was initially diagnosed with a mitochondrial disorder, based in part upon nonspecific muscle biopsy findings, but mitochondrial DNA mutation analysis revealed no mutations. Whole exome sequencing revealed compound heterozygosity for two EPG5 variants, inherited in trans . One was a known pathogenic mutation in exon 13 (c.2461C > T, p.Arg821X). The second was reported as a variant of unknown significance found within intron 16, six nucleotides before the exon 17 splice acceptor site (c.3099‐6C > G). Reverse transcription‐polymerase chain reaction of the EPG5 mRNA showed skipping of exon 17—which maintains an open reading frame—in 77% of the transcript, along with 23% expression of wild‐type mRNA suggesting that intronic mutations may affect splicing of the EPG5 gene and result in symptoms. However, the expression of 23% wild‐type mRNA may result in a significantly attenuated Vici syndrome phenotype.